2004
DOI: 10.1002/pola.20510
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of monosubstituted and disubstituted poly(3,4‐propylenedioxythiophene) derivatives with high electrochromic contrast in the visible region

Abstract: Monosubstituted and disubstituted 3,4‐propylenedioxythiophenes were synthesized and polymerized by both chemical and electrochemical methods. All the monomers were characterized for their molecular structures, and the polymers were characterized for their electrochemical properties. The disubstituted derivatives showed higher contrast than the corresponding monoalkyl derivatives. The highest electrochromic contrast of 89% was exhibited by a dibenzyl derivative, but the derivative was insoluble. On the other ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0
4

Year Published

2007
2007
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 27 publications
2
30
0
4
Order By: Relevance
“…The weight-average molecular weight of POOT was 1700, whereas the polydispersity index was 1.36. The weight-average molecular weight was smaller, and the polydispersity index was larger than that of the soluble polythiophene derivatives synthesized by Mishra et al 18 The adoption of different polymerization media may contribute to these differences.…”
Section: Figurementioning
confidence: 96%
See 1 more Smart Citation
“…The weight-average molecular weight of POOT was 1700, whereas the polydispersity index was 1.36. The weight-average molecular weight was smaller, and the polydispersity index was larger than that of the soluble polythiophene derivatives synthesized by Mishra et al 18 The adoption of different polymerization media may contribute to these differences.…”
Section: Figurementioning
confidence: 96%
“…31 The Potential Difference of the Redox Peaks (DE p ) values of the polymer film increased with increasing scanning rate, which indicated that the redox process of the polymers was quasireversible. 18 In this study, cyclic voltammetry was exploited as a method for evaluating the stability of the polymer. For this purpose, we accomplished nonstop cycling of the applied potential between 2550 and 1850 mV at a scanning rate of 100 mV/s.…”
Section: Polymer Electrochemistrymentioning
confidence: 99%
“…[5][6][7] Of the available electrochromic materials, conjugated conducting polymers have become widely researched electrochromic materials because of their fast switching speeds, improved processability, and color tunability through structural modification. [8][9][10][11][12] Recently, our group has produced a series of alkyland alkoxy-substituted poly(3,4-propylenedioxythiophene)s (PProDOTs) that are soluble in common organic solvents and therefore easily processable by spin-coating or spray-casting. [13] The branched polymer (bis(ethylhexyloxy)-substituted PPro-DOT, PProDOT-(CH 2 OEtHx) 2 ), has been investigated as the active layer in a reflective electrochromic device (ECD), switching between highly absorbing and highly reflecting states.…”
Section: Introductionmentioning
confidence: 99%
“…Synthesis and characterizations of poly (3,4-propylenedioxythiophene) (PProDOT) and its derivatives were first reported by Reynolds et al [19] and the derivatives were shown to exhibit high in situ conductivity, color tunability, high coloration efficiency and fast response time [20]. Kumar et al studied the mono and disubstituted PProDOT derivatives for EC applications, and they reported that the disubstituted polymer derivatives show high color contrast than the corresponding mono substituted polymers [21].…”
Section: Introductionmentioning
confidence: 96%